ISLAMIC ECOTHEOLOGY AND ENVIRONMENTAL SUSTAINABILITY: A SYSTEMATIC LITERATURE REVIEW OF CONCEPTUAL FRAMEWORKS, METHODOLOGICAL APPROACHES, AND RESEARCH TRAJECTORIES - Much. Hasan Darojat; Sofwan Manaf; Duna Izfanna; Rokimin Rokimin (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Background: The worsening global environmental crisis requires a values-based approach that goes beyond conventional policy frameworks. In this context, Islamic ecotheology offers an ethical perspective relevant to the principles of sustainability. Research Objective: To identify publication trends, dominant theoretical frameworks, and patterns of integration between religious environmental ethics and sustainability practices in Islamic ecotheology literature. The method used was a systematic literature review (SLR) following PRISMA guidelines. A search was conducted through Scopus using nine keyword combinations, resulting in 847 initial records. After applying inclusion criteria (period 2015–2025, journals indexed Q1–Q4, topic relevance), 80 full articles were analyzed using bibliometric profiles and qualitative thematic synthesis with the Watase Uake system. The research findings show a dominance of qualitative methods (75%) and a bipolar geographical distribution between Muslim-majority developing countries and Western academic institutions. Thematic concentrations fall into four main clusters: theological concepts (44%), sustainability practices (35%), environmental ethics (25%), and interpretation of religious texts (19%). This research also identified important gaps, including the limited use of quantitative methods, minimal policy-practice linkages, and a lack of cross-religious comparative studies. In conclusion, Islamic ecotheology offers a transformational ethical framework for raising environmental awareness. Future research should focus on the development of standardized measurement instruments, policy-based research, and interfaith dialogue to enhance scientific rigor and practical impact.